Evaluation of the Antioxidant and Antimicrobial Activity of Ziziphora clinopodiodes Essential Oil Eluted at Different Times - Alizadeh, Mojgan; Arianfar, Akram; Mohammadi, Ameneh (Current Bioactive Compounds, 2021)
Objective: Ziziphora clinopodioides is an edible medicinal plant belonging to the Labiatae family that is widespread all over Iran. It used in culinary and also in cold and cough treatments in Iran. The aim of the present work was to evaluate the effect of different timeframes during hydrodistillation on essential oil composition, antimicrobial and antioxidant activity. Materials and Methods: The essential oil of Z. clinopodiodes was extracted via hydrodistillation with Clevenger apparatus. The fractions of essential oil were captured at 6 times from the beginning of the distillation: (10, 20, 60, 120, 180 and 240 min). The fractions of essential oil were analyzed by GC/MS and their antibacterial, antifungal and antioxidant activities were studied by Disk - well diffusion and DPPH methods, respectively. Results: Six distillation times and whole essential oil were captured during hydrodistillation. Essential oil yield dropped off significantly during distillation progressed (1.0% for 10 min and 0.025 for 240 min). 1,8 Cineol, Isomenthone, Pulegone, Piperitenone and Citronellic acid were major compounds in fractions and they were affected by distillation times. Pulegone was a major compound in all of the essential oils. In antioxidant activity assay, whole essential oil was stronger than positive control and fractions of essential oil, because of higher levels of Isomenthone, Piperitenone and Citronellic acid. Strongest antimicrobial activity against S. aureus, E. coli and C. albicans was observed from 10 min fraction. Conclusion: Our results indicated that distillation time can create essential oils with specific properties and we can achieve more efficient essential oil in short times.
Keywords: different timeframes